Cyber cheating: the new chalenge to the educators / Intan Marzita Saidon and Nadzri Ab. Ghani - Saidon, Intan Marzita; Ab. Ghani, Nadzri (2002)
Cheating behavior among students is an "evergreen" issue to the educators. Copying other students work, carrying reference materials in the examination hall and sharing information inappropriately are some examples of the outdated styles of cheating. Nowadays, educators are facing the new "art" of cheating: cyber cheating. This paper addresses this issue. It explains how the Internet as the main source of information has indirectly opened this new avenue to cheat. It follows with a discussion on several proposed strategies to prevent the widespread of this cheating style among students. A brief conclusion regarding this issue ends this paper.